HYPERTENSION, PREECLAMPSIA AND ECLAMPSIA AMONG HIV-INFECTED PREGNANT WOMEN FROM LATIN AMERICA AND CARIBBEAN COUNTRIES - Machado, Elizabeth Stankiewicz (2014)
OBJECTIVES: To evaluate the incidence of and risk factors for hypertensive disorders in a cohort of HIV-infected pregnant women. METHODS: Hypertensive disorders (HD) including preeclampsia/eclampsia (PE/E) and pregnancy-induced hypertension, and risk factors were evaluated in a cohort of HIV-infected pregnant women from Latin America and the Caribbean enrolled between 2002-2009. Only pregnant women enrolled for the first time in the study and delivered at ≥ 20 weeks gestation were analyzed. RESULTS: HD were diagnosed in 73 (4.8%, 95%CI: 3.8%-6.0%) of 1513 patients; 35(47.9%) had PE/E. HD was significantly increased among women with a gestational age-adjusted body mass index (gBMI) ≥ 25 kg/m(2) (OR=3.1; 95%CI: 1.9-5.0), hemoglobin (Hg) ≥11 g/dL at delivery (OR=2.1; 95%CI: 1.2-3.6) and age ≥35 years (OR=1.8; 95%CI: 1.1-3.2). PE/E was increased among women with a gBMI ≥25 kg/m(2) (OR=3.0; 95%CI: 1.5-6.0) and Hg ≥11 g/dL at delivery (OR=2.8; 95%CI: 1.2-6.5). A previous history of PE/E increased the risk of PE/E 6.7 fold (95%CI: 1.8-25.5). HAART before conception was associated with PE/E (OR=2.3; 95%CI: 1.1-4.9) CONCLUSIONS: HIV-infected women, with a previous history of PE/E, a gBMI ≥25 kg/m(2), Hg at delivery ≥11 g/dL and in use of HAART before conception are at an increased risk of developing PE/E during pregnancy.